2003
DOI: 10.1097/00024720-200304000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Is INFUSE Bone Graft Superior to Autograft Bone? An Integrated Analysis of Clinical Trials Using the LT-CAGE Lumbar Tapered Fusion Device

Abstract: Multicenter human clinical studies of patients undergoing anterior lumbar fusion have been conducted using recombinant bone morphogenetic protein or rhBMP-2 on an absorbable collagen sponge, marketed as INFUSE Bone Graft, or autograft implanted in the LT-CAGE Lumbar Tapered Fusion device. An integrated analysis of multiple clinical studies was performed using an analysis of covariance to adjust for preoperative variables in a total of 679 patients. Of these patients, 277 had their cages implanted with rhBMP-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(164 citation statements)
references
References 15 publications
8
152
0
4
Order By: Relevance
“…Use of rhBMP-2 and other bone morphogenetic proteins for enhancing osteoblastic activity and accelerating spinal fusion is well documented [2,4,7,10]. Observations from this study also showed that an improvement in clinical outcome was seen in all patients.…”
Section: Discussionsupporting
confidence: 62%
“…Use of rhBMP-2 and other bone morphogenetic proteins for enhancing osteoblastic activity and accelerating spinal fusion is well documented [2,4,7,10]. Observations from this study also showed that an improvement in clinical outcome was seen in all patients.…”
Section: Discussionsupporting
confidence: 62%
“…The clinical performance of each of these products has been comparable to autografts in certain BTE applications [55,56], and both products have received FDA approval for limited indications [55,57].…”
Section: Bmp-2mentioning
confidence: 99%
“…This particular carrier was optimized for use in the interbody space inside a structural element (cage), and higher doses (up to 40 mg) with composite carriers composed of collagen and ceramic have been optimized for use in posterolateral spinal fusion but have not yet gained FDA approval [18][19][20][21] . Achievement of radiographic evidence of successful interbody fusion with this technique can be as high as 98% on the basis of computed tomographic (CT) scan evaluation, with superiority over autogenous bone graft 22 . Moreover, recent data based on review of a large administrative database [23][24][25] suggest that INFUSE can be effective in patients who are older than sixty years and in patients who smoke and that INFUSE does not result in increased complications (except when used in high doses in the cervical spine).…”
Section: Current Status Of Osteoinductive Agents For Spine Fusionmentioning
confidence: 99%